Hemisection as an Alternative Treatment for Mandibular Molars with Separated Instrument: A Case Report - Ateeq-ur-Rehman; Bader Munir (Journal of University Medical & Dental College, 2022)
Hemisection is a procedure involving the removal of an untreatable root with an accompanied crown portion while saving the other healthy root with adequate bone support. This case report represents the treatment of 2nd mandibular molar with irretrievable and unable to bypass separated instruments in the mesiobuccal canal of the mesial root. After sectioning the tooth, mesial root with the crown portion was extracted, and the remaining part of the tooth was restored as a premolar. Restorative rehabilitation was done by cementing a three-unit metal ceramic bridge. The good outcomes of endodontic treatment and patient demand towards the conservation of tooth encouraged the procedure of hemisection. For the preservation of terminal mandibular molars with irretrievable and unable to bypass separated instruments, hemisection can be considered as an alternative treatment option our objective is to conserve terminal mandibular molar with adequate bone support as a replacement in this area is complex, time consuming, and costly.